Effect of Gibberellin (GA3) Application on the Growth Rate of Hydroponic Alfalfa (Medicago sativa L.) Fodder - Ahimsa Kandi Sariri; Sri Lestari (Jurnal Biologi Tropis, 2026)
Feed is a major component in livestock production; however, the availability of forage is often constrained by limited land resources and seasonal fluctuations. A leguminous plant, alfalfa (Medicago sativa L.) is sometimes referred to as the "queen of forages" because of its abundant protein and great nutritional value. Forage production might be improved by using the plant growth regulator gibberellin (GA3). The purpose of this research was to find out how much of an impact GA3 has on the pace of growth of alfalfa fodder, taking into account factors like germination time, plant height, and biomass output (both fresh and dry weight). P0 (control group without GA3), P1 (GA3 150 ppm), and P2 (GA3 300 ppm) were the three treatments in this completely randomised design trial with four replications. Time to germination, plant height, fresh weight, and dry weight of alfalfa feed were some of the noted factors. The findings showed that out of the three treatments, P0 (21.25 hours), P2 (20.30 hours), and P1 (19.45 hours) had the quickest germination times.The highest plant height was recorded in P2 (4.24±1.99 cm), followed by P1 (3.79±1.83 cm) and P0 (3.09±1.90 cm). The highest fresh weight was also observed in P2 (24.75±1.89 g), while the highest dry weight was found in P0 (10.00±0.85%). Statistical analysis indicated that GA3 application had a significant effect on germination time but did not significantly affect plant height, fresh weight, and dry weight. It can be concluded that GA3 application effectively accelerates the germination of alfalfa; however, it does not significantly improve biomass production of alfalfa fodder.